Implementasi Algoritma Seal Pada Pengamanan Data Penjualan Tiket PT. Amanda Tour & Travel - Suwondo, Suwondo (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
- SEAL is a type of stream cipher, which processes units or input data, messages or information at one time. Units or data are generally bytes. In this way, encryption or decryption can be performed on variable lengths. This algorithm does not have to wait for a certain amount of input data, messages or information before processing, or add additional bytes for encryption. The encryption technique used in the SEAL algorithm is to encrypt and decrypt each input data to secure customer data at PT. Amanda Tour & Travel, a travel company in Medan that provides airline ticket booking services. To prove the encryption results, direct access to the system is demonstrated by applying the SEAL algorithm stored in the database using a database access interface. The cryptographic algorithm to be used in securing PT. Amanda Tour & Travel is a symmetric cryptographic algorithm and a stream cipher, so that the encrypted data (ciphertext) has the same size as the original data (plaintext). Symmetric cryptography was chosen because it is expected that this algorithm will securely encrypt and decrypt customer data.